Leveraging Relay Nodes to Deploy and Update Services in a CPS with Sleeping Nodes - Omond, Antoine Stephane Pierre Guy; Coullon, Hélène; Rais, Issam; Anshus, Otto Johan (IEEE, 2024)
Cyber-physical systems (CPS) deployed in scarce resource environments like the Arctic Tundra face extreme conditions. Nodes in such environments are forced to rely on batteries and sleep most of the time to maximize their lifetime. While being autonomous, nodes have to collaborate to make scientific observations. As a result, their deployments and updates are subject to coordination (e.g., prevent interruption of a service used by other nodes). In this paper, we study analytically and experimentally, to what extent using relay nodes for communications reduces the deployment and update durations, and which factors influence this reduction. Intuitively, as dealing with sleeping nodes with low chances of uptime overlaps (no uptime synchronization), a coordinated deployment or update takes very long to finish if nodes have to communicate directly.